Ensuring That an Equity, Diversity, Inclusion, and Anti-racism Pledge Promotes Meaningful Change: Words and Actions. (12th October 2021) - Ebong, Ima M.; Spector, Andrew R.
Abstract : Racism has been a part of academic medicine, including in neurology, for generations. While some neurology departments had an infrastructure to promote diversity and inclusion prior to 2020, several high-profile events that occurred that year—including the murders of George Floyd, Breonna Taylor, and Ahmaud Arbery, nationwide protests over police brutality and White supremacy, as well as the disproportionate impact of the COVID-19 pandemic on people of color—catapulted anti-racism onto the agendas of academic departments across the country. In the last year, many neurology departments have appointed diversity officers. Statements condemning racism and supporting equity, diversity, and inclusion are now featured prominently on neurology program webpages, and neurology training programs promote their efforts to foster equity, diversity, and inclusion (EDI) on social media to attract more applications from physicians from groups that are underrepresented in medicine. These encouraging changes suggest that neurology department leaders recognize the importance of EDI, anti-racism, and social justice, but are they committing their departments to action or simply reacting to the social climate?